Species integrity enhanced by a predation cost to hybrids in the wild. (26th July 2017) - Nilsson, P. Anders; Hulthén, Kaj; Chapman, Ben B.; Hansson, Lars-Anders; Brodersen, Jakob; Baktoft, Henrik; Vinterstare, Jerker; Brönmark, Christer; Skov, Christian
Abstract : Species integrity can be challenged, and even eroded, if closely related species can hybridize and produce fertile offspring of comparable fitness to that of parental species. The maintenance of newly diverged or closely related species therefore hinges on the establishment and effectiveness of pre- and/or post-zygotic reproductive barriers. Ecological selection, including predation, is often presumed to contribute to reduced hybrid fitness, but field evidence for a predation cost to hybridization remains elusive. Here we provide proof-of-concept for predation on hybrids being a postzygotic barrier to gene flow in the wild. Cyprinid fishes commonly produce fertile, viable hybrid offspring and therefore make excellent study organisms to investigate ecological costs to hybrids. We electronically tagged two freshwater cyprinid fish species (roach Rutilus rutilus and bream Abramis brama ) and their hybrids in 2005. Tagged fish were returned to their lake of origin, exposing them to natural predation risk from apex avian predators (great cormorant, Phalacrocorax carbo ). Scanning for regurgitated tags under cormorant roosts 3–4 years later identified cormorant-killed individual fish and allowed us to directly test for a predation cost to hybrids in the wild. Hybrid individuals were found significantly more susceptible to cormorant predation than individuals from either parental species. Such ecological selection against hybrids contributes to species integrity, and can enhance species diversification.